Transperineal ultrasound-guided prostate biopsy is safe even when patients are on combination antiplatelet and/or anticoagulation therapy - Kimitoshi Saito; Satoshi Washino; Yuhki Nakamura; Tsuzumi Konishi; Masashi Ohshima; Yoshiaki Arai; Tomoaki Miyagawa (BMC Urology, 2017)
Abstract Background To assess whether hemorrhagic complications associated with transperineal prostate biopsy increased in patients on antiplatelet and/or anticoagulant therapy. Methods In total, 598 consecutive patients underwent transperineal prostate biopsy. The medication group comprised patients who took anti-thromboembolic agents, and the control group comprised those who did not take these agents. No anti-thromboembolic agent was stopped before, during, or after prostate biopsy in the medication group. Complications developing in both groups were compared and classified using the modified Clavien classification system. Subgroup analyses to compare complications in patients taking single antiplatelet, single anticoagulant, and dual antiplatelet and/or anticoagulant agents, and multivariate analyses to predict bleeding risk were also performed. Results Of the 598 eligible patients, 149 comprised the medication group and 449 comprised the control group. Hematuria (Grade I) developed in 88 (59.1%) and 236 (52.5%) patients in the medication and control group, respectively (p = 0.18). Clot retention (Grade I) was more frequently observed in the medication group than the controls (2.0% versus 0.2%, respectively, p < 0.05). Hospitalization was more frequently prolonged in the medication than the control group (4.0% versus 0.4% of patients, respectively). No complication of Grade III or higher developed in either group. Hematuria was more frequent in patients taking a single anticoagulant (p = 0.007) or two anti-thromboembolic agents (p = 0.04) compared with those taking a single antiplatelet agent. Other complications were generally similar among the groups. In the multivariate analysis, taking more than two anti-thromboembolic agents was the only significant risk factor for bleeding events. Conclusion No severe complication developed after the transperineal biopsies in either group, although minor bleeding was somewhat more frequent in the medication group. It may not be necessary to discontinue anticoagulant and/or antiplatelet agents when transperineal prostate biopsy is contemplated.